Growth Pattern and Condition Factor of Spinner Shark Carcharhinus brevipinna in Southern Nusa Tenggara Waters - Sentosa, Agus Arifin; Fahmi, Fahmi; Chodrijah, Umi (Indonesian Institute of Sciences, 2018)
The spinner sharks are one of shark commodities that are utilized optimally from the southern of Nusa Tenggara waters, however, the scientific information is still limited. This study aimed to assess the growth pattern and condition factors of the spinner shark, Carcharhinus brevipinna in southern Nusa Tenggara waters. The research was conducted from January to December 2016 using direct recording of the catch data. Information on length, weight and sex determinations were collected by the enumerator. The data was analysed descriptively with the shark condition was determined based on the relative condition factor obtaining from the length-weight relationship. The results showed that growth patterns of the spinner shark, both males and females, were allometrically negative. The relative condition factors of the catch of male sharks were ranged from 0.206 Ã¢Â€Â“ 2.225Ã‚Â and females from 0.237 Ã¢Â€Â“ 3.361. The condition factors of spinner sharks were not different between sexes and time of fishing, but they were different in length classes